The Impact of Contextual Authentic Materials on Reading Comprehension among Vocational High School Learners - Zulkifli Surahmat; Ahmad Risal Majid; Agnez; Sitti Hadija; Peter John Wanner (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study investigates the effectiveness of using contextual authentic materials in improving vocational high school (SMK) students’ reading comprehension and motivation in learning English reading. The research was conducted among tenth-grade hospitality students at SMK Negeri 2 Polewali during the 2025/2026 academic year. Using a quasi-experimental nonequivalent control group design, 42 students were randomly assigned to experimental (n = 21) and control (n = 21) groups. The experimental group was taught using contextual authentic materials, such as hotel advertisements, reservation forms, tourism brochures, and workplace memos—while the control group received conventional textbook-based instruction over six sessions within five weeks. Data were collected through pretests and posttests consisting of 20 multiple-choice items measuring four sub-skills: identifying main ideas, recognizing supporting details, making inferences, and interpreting references. Statistical analyses using SPSS version 26 included descriptive statistics, assumption testing, and inferential analyses (ANCOVA and independent-samples t-test). The results revealed that the experimental group outperformed the control group significantly, F(1, 39) = 26.48, p < .001, partial η² = .40, with a large effect size (Cohen’s d = 1.62). Students exposed to contextual authentic materials demonstrated greater gains across all sub-skills, with the highest improvement in inference-making. Classroom observations further indicated that these materials enhanced students’ engagement and motivation by linking classroom learning to real-world professional contexts. The findings affirm that contextual authentic materials are effective in fostering both cognitive and affective outcomes in vocational English learning. They enable students to connect language learning with their future careers, promoting meaningful, relevant, and motivated reading comprehension. Consequently, English teachers and curriculum developers in vocational schools are encouraged to integrate authentic vocational texts into instruction to bridge the gap between classroom learning and workplace communication.